(untitled) (Revista Científica Integrada, 2024)
Objective: To identify the personality traits of individuals undergoing treatment for Tuberculosis in Family Health Centers and their relationship with therapeutic adherence. Method: descriptive, cross-sectional, correlational study. 89 people from 35 Family Health Centers were interviewed. Big Five Inventory, pill count technique and sociodemographic data were used. Results: 85.4% were adherent and 12.4% registered relapses or readmissions due to previous abandonments. The responsible personality trait presented a significant relationship with adherence (p=0.006). Conclusion: This research managed to identify the existing personality traits in patients with Tuberculosis and predict which personality characteristics favor adherence to therapy. This assessment detected a great need to incorporate strategies for assessing the mental health of patients, due to because these favor therapeutic adherence.